Model Kelas Penyelenggara Pendidikan Inklusif di SDN Medan - Dahniar Harahap; Nina Hastina (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2019)
This study aims to reveal the existence and type of students with special needs in elementary school (SD) providers of inclusive education in the city of Medan. The research subjects included 4 elementary schools in Marelan Medan. Collecting data from the results of observations, interviews and documentation. The results of the analysis show that 2 schools place students in regular classes with clusters, 1 school with regular classes with pull outs and 1 full special class school. Types of students who have special needs consist of 52% mild mental retardation, 30% moderate mental retardation, 17% learning difficulties and 1% deaf. It is recommended to place students in each regular class and accept students in placements in public schools. Penelitian ini bertujuan untuk mengungkapkan keberadaan dan jenis siswa berkebutuhan khusus di Sekolah Dasar (SD) penyelenggara pendidikan inklusif di kota Medan. Subjek penelitian meliputi 4 SDN di Medan Marelan. Pengumpulan data dari hasil observasi, wawancara dan dokumentasi. Hasil analisis menunjukkan 2 sekolah menempatkan siswa pada kelas reguler dengan cluster, 1 sekolah dengan kelas reguler dengan pull out dan 1 sekolah kelas khusus penuh. Jenis siswa yang memiliki kebutuhan khusus terdiri dari 52% tunagrahita ringan, 30% tunagrahita sedang, 17% kesulitan belajar dan 1% tunarungu. Direkomendasikan untuk menempatkan siswa di setiap kelas reguler dan menerima siswa dalam penempatan di sekolah umum.